Pembelajaran Membaca dan Menulis Permulaan dengan Metode Iqro bagi Siswa Kelas Awal Sekolah Dasar - Supriyadi Supriyadi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2000)
Iqro Method for Teaching Reading and Writing in the Early Years of Elementary School. The study was aimed at finding alternatives for teaching reading and writing in the early years of elementary school. The Iqro method, which is known as the successful method of learning Arabic, was adapted and modified into the teaching and learning of Indonesian. An action research design was employed, involving 22 first graders of SDN Sumbersari 3, Malang. The findings indicate that this modified method facilitated and advanced students' ability in reading and writing.